Getting started with Windows Server Security : develop and implement a secure Microsoft infrastructure platform using native and built-in tools - Sivarajan, Santhosh (Professional expertise distilled., 2015)
If you are a security or Windows Server administrator wanting to learn or advance your knowledge in Microsoft security and secure your Windows Server infrastructure effectively, this book is for you.